Implementasi Gerakan Literasi Sekolah Dalam Meningkatkan Kemampuan Membaca Di MI KHR Ilyas Maduretno - Indriyani, Juni; Rinawati, Atim; Murtopo, Bahrun Ali (IAINU Kebumen, 2022)
The study aims to find out how the implementation of the School Literacy Movement (GLS) for class II MI KHR Ilyas Maduretno students and what are the supporting factors and inhibiting factors in the implementation of the School Literacy Movement (GLS) in improving the reading skills of class II MI KHR Ilyas Maduretno students. In this study using a qualitative approach by processing the data obtained in the field. The researcher acts as an observer of the implementation of the School Literacy Movement (GLS) in improving students reading skills at MI KHR Ilyas Maduretno, the research instrument used is to use data collection techniques through observations, interviews, documentation and perform data analysis with data reduction, data presentation then draw conclusions. The results of the study found that the implementation of the School Literacy Movement (GLS) for class II MI KHR Ilyas Maduretno students was still at the stage of habituation. One form of habituation cultivation is through the application of reading 15 minutes every day before learning begins. Supporting factors in implementating the School Literacy Movement (GLS) program are: (1) availability of reading corners in class II, (2) strategies used to increase student enthusiasm through mentoring and student internship programs, while inhibiting factors include: (1) insufficient availability of books, (2) libraries that are not well organized, and (3) lack of student motivation. Key Words: Implementation, School Literacy Movement, Reading Skills